2020
DOI: 10.1302/0301-620x.102b7.bjj-2019-1263.r2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on outcome and revision in total ankle arthroplasty

Abstract: Aims To assess the effect of age on clinical outcome and revision rates in patients who underwent total ankle arthroplasty (TAA) for end-stage ankle osteoarthritis (OA). Methods A consecutive series of 811 ankles (789 patients) that underwent TAA between May 2003 and December 2013 were enrolled. The influence of age on clinical outcome, including the American Orthopaedic Foot and Ankle Society (AOFAS) hindfoot score, and pain according to the visual analogue scale (VAS) was assessed. In addition, the risk for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 33 publications
0
21
2
Order By: Relevance
“…Nevertheless, some recent studies regarding modern TAA have questioned the indication of TAA in young patients. Satisfying outcomes including implant survival and reoperation rates with no significant difference to older patients have been more often reported recently [17][18][19][20]22,23], which is clearly in contrast to the findings of this study. For example, a retrospective cohort study conducted by Gaugler et al using the Hintegra implant in a cohort of 811 patients revealed no significant effect of age on the rates for minor or major revisions, while the clinical outcomes of younger and older patients were comparable with slightly better pain relief in older patients [20].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, some recent studies regarding modern TAA have questioned the indication of TAA in young patients. Satisfying outcomes including implant survival and reoperation rates with no significant difference to older patients have been more often reported recently [17][18][19][20]22,23], which is clearly in contrast to the findings of this study. For example, a retrospective cohort study conducted by Gaugler et al using the Hintegra implant in a cohort of 811 patients revealed no significant effect of age on the rates for minor or major revisions, while the clinical outcomes of younger and older patients were comparable with slightly better pain relief in older patients [20].…”
Section: Discussioncontrasting
confidence: 99%
“…Satisfying outcomes including implant survival and reoperation rates with no significant difference to older patients have been more often reported recently [17][18][19][20]22,23], which is clearly in contrast to the findings of this study. For example, a retrospective cohort study conducted by Gaugler et al using the Hintegra implant in a cohort of 811 patients revealed no significant effect of age on the rates for minor or major revisions, while the clinical outcomes of younger and older patients were comparable with slightly better pain relief in older patients [20]. Similarly, Lee et al reported no significant difference in revisions rates and clinical outcomes related to age at time of surgery when using the Hintegra implant in a cohort of 117 patients [17].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Conversely, in a prospective study with a database of 538 ankle replacements, four implants (INBONE I, INBONE II, STAR, and Salto-Talaris) were used and age was not associated with higher failure rates in a multivariable logistic regression analysis 30 . A retrospective study 32 of 811 HINTEGRA total ankles reported that clinical outcomes and the probability of revision surgery after TAA were comparable between young and old patients; the risk of revision surgery is not affected by age.…”
Section: Discussionmentioning
confidence: 99%